The Effects of Youth Political Participation on Political Awareness and Perception in Indonesia: a Systematic Review and Meta-Analysis - Gede Wikan Pradnya Dana; Teddy Chrisprimanata Putra; I Komang Agus Widiantara (Poltanesa, 2026)
Youth political participation, particularly among university students and novice voters, serves as a crucial element in dynamizing democracy and driving socio-political change in Indonesia. While the digital era has significantly expanded participatory channels ranging from offline institutional movements to contemporary digital activism, the quantitative impact of these multidimensional activities on actual cognitive outcomes remains largely unsynthesized. The existing empirical evidence is highly fragmented, necessitating a comprehensive evaluation. Therefore, this study aims to systematically estimate the correlation strength between youth political participation and their levels of political awareness and democratic perception. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this research synthesized 12 primary quantitative studies comprising a total of 2,345 youth participants. The statistical analysis utilized a Random Effects Model to accommodate contextual diversity, alongside Egger's regression and funnel plot analysis to rigorously evaluate publication bias. The analytical results reveal a highly robust, statistically significant positive correlation [] between political involvement and cognitive maturation, despite substantial inter-study heterogeneity (I-squared = 94%). Subsequent bias detection objectively confirmed the absence of the file-drawer problem, ensuring the reliability of the pooled estimate. Ultimately, this meta-analysis empirically confirms that active youth participation substantially functions as a school of democracy that accelerates cognitive mobilization. The findings offer a solid empirical foundation for educational stakeholders, electoral commissions, and student organizations to design evidence-based political education programs and digital literacy interventions to safeguard novice voters against electoral disinformation.